Social, Economical and Environmental Issues of Floriculture Sector Development in Ethiopia - Tizazu, Tadele Yeshiwas; Workie, Melkamu Alemayehu (Review of Plant Studies, 2018)
The floriculture sector is a new agricultural industry in Ethiopia. The sector created job opportunities for thousands of people especially women and generates huge amount of foreign exchange earnings to the country. However, it’s social and environmental issues associated with the development of the sector are not yet well documented. The present review was therefore initiated with the objective to summarize and the sector development and document the issues raised associated with its development in the country. According to the review results the floriculture industry is suffering from insufficient infrastructure system necessary for further development of the industry which should be solved with the respective stakeholders. Moreover, the industry is accused from negative environmental and social impacts which may have negative impacts for future development of the industry. Continuous awareness trainings on health and safety issues through respective stakeholders and regular monitoring in the implementation of guidelines and roles regarding environmental protection is recommended to sustain the further improvement of the industry in Ethiopia.